Predators of Lymantria dispar (Lep. Lymantriidae) egg masses: Spatio-temporal variation of their impact during the 1988-89-pest generation in the Mamora cork oak forest (Morocco). - Villemant, C; Ramzi, H (ENTOMOPHAGA, 1995)
In the Mamora cork oak forest (Morocco), oophagous predators of the gypsy moth Lymantria dispar (L.) (Lepidoptera: Lymantriidae) are one of the main mortality factors influencing pest population dynamics. The predators destroy egg masses more by disrupting their cohesiveness than by predation. From 1987 to 1990, the impact of oophagous enemies significantly contributed to the collapse of a localized gypsy moth outbreak. Variation of egg mass dislocation intensity was greater between trees than among the different strata of a tree. The number of gypsy moth egg masses and egg predator attacks increased when oaks were large and unhealthy. Forest degradation probably explains why egg mass destruction rates were so high (60 to 90% of the eggs) in the infested forest. Oophagous predators find food and shelter under the dehiscent bark of unhealthy cork oaks.
Keywords: Cork oak; egg predator; Gypsy moth; Population Dynamics; spatial distribution